2020
DOI: 10.3390/cancers12113459
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy Moves to the Early-Stage Setting in Non-Small Cell Lung Cancer: Emerging Evidence and the Role of Biomarkers

Abstract: Despite numerous advances in targeted therapy and immunotherapy in the last decade, lung cancer continues to present the highest mortality rate of all cancers. Targeted therapy based on specific genomic alterations, together with PD-1 and CTLA-4 axis blocking-based immunotherapy, have significantly improved survival in advanced non-small cell lung cancer (NSCLC) and both therapies are now well-established in this clinical setting. However, it is time for immunotherapy to be applied in patients with early-stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 117 publications
0
7
0
Order By: Relevance
“…Immune checkpoint inhibitors (ICIs) have revolutionized the therapeutic scenario against advanced lung cancers and have been gradually applied for the treatment of early-stage lung cancers. 8 Preliminary small-sample studies have revealed that most high-risk GGOs in patients with stage I or advanced non-small cell lung cancer (NSCLC) have no diameter reduction after receiving ICIs. 9 10 Therefore, exploring the distribution of predictive biomarkers of immunotherapy in patients with MPLC is important to evaluate the application value of ICIs in this group of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Immune checkpoint inhibitors (ICIs) have revolutionized the therapeutic scenario against advanced lung cancers and have been gradually applied for the treatment of early-stage lung cancers. 8 Preliminary small-sample studies have revealed that most high-risk GGOs in patients with stage I or advanced non-small cell lung cancer (NSCLC) have no diameter reduction after receiving ICIs. 9 10 Therefore, exploring the distribution of predictive biomarkers of immunotherapy in patients with MPLC is important to evaluate the application value of ICIs in this group of patients.…”
Section: Introductionmentioning
confidence: 99%
“…In both cases, concurrent or sequential therapy, a consolidation with durvalumab, an immune checkpoint inhibitor (ICI), is approved according to the results of PACIFIC trial ( Antonia et al, 2017 ). ICIs are currently being evaluated as neoadjuvant/adjuvant therapy in combination with standard treatments ( Mielgo-Rubio et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is urgently needed to explore novel treatment strategies to reduce the tumor burden and improve the pCR rate, and prolong the survival of LSqCC patients whose tumors are potentially unresectable. Emerging data from clinical trials have demonstrated that immunotherapy substantially improves the survival of patients with late-stage NSCLC, including advanced LSqCC (5,6,26), and has also clinical promise in early-stage NSCLC (27). However, in the real-world setting, studies specifically investigating neoadjuvant immunotherapy followed by surgery for locally-advanced and surgically difficult LSqCC are lacking.…”
Section: Discussionmentioning
confidence: 99%